Penerapan Model Jigsaw Untuk Meningkatkan Keterampilan Gerak Tari Siswa di Sekolah Dasar - Indriyani, Dewi; Nurasiah, Iis; Nurmeta, Irna Khaleda (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to determine the improvement of students' dance movement skills in elementary school through the application of cooperative models. The research method used was Kemmis and Mc Taggart design class action research. The research was conducted at SD Negeri Datar Limus with the research subject being class II of SD Negeri Datar Limus. Data were collected through observation, tests, and documentation and then analyzed using descriptive statistical techniques. The results showed that there was an increase in students' dance movement skills as evidenced by students becoming more proficient in performing basic movements of the hands, feet, and head and coordinating the three basic movements.  The results of the student dance skills test showed that in the pre-cycle the average value obtained by students was 55.68 with classical completeness reaching 32%. Then in cycle I, the average value obtained was 65.72 with classical completeness reaching 52%. The average value obtained in cycle II was 80.12 with classical completeness reaching 80%.